Oblicz:
a) (3a+4)(a-5)=
b) (√3+1)(2√3-2)=
c) (x+2√2)²=
d) (4y+3)(y-2)-2y(4-2y)=
e) 2(3a²-1)-(a+2)(a+2)=
f) 5x²(v²+1)-(x²-2)(x²+3)=
g) -(3c-2)(c-1)-c(c-2)=
h) 2x²(x-5)-3x(x²-3x+5)=
i) 6(a²+b+⅓)-6(a²-½)-3(b+⅓)=
j) 6x+12y/3+x-4y=
k) 4*3p+6/12+10-p/15-9=

2

Odpowiedzi

2009-10-03T14:36:52+02:00
A) (3a+4)(a-5)= 3a²- 15a + 4a - 20 = 3a² - 11a - 20
b) (√3+1)(2√3-2)= 6 - 2√3 + 2√3 - 2 = 4
c) (x+2√2)²= x² + 4√2 + 8
d) (4y+3)(y-2)-2y(4-2y)= 4y² - 8y + 3y - 6 - 8y + 4y² = 8y² - 13y - 6
e) 2(3a²-1)-(a+2)(a+2)= 6a² - 2 - a² - 2a - 2a - a = 5a² - 5a - 2
f) 5x²(x²+1)-(x²-2)(x²+3)= 5x⁴ + 5x² - x⁴ - 3x² + 2x² + 6 = 4x⁴ + 4x² + 6
g) -(3c-2)(c-1)-c(c-2)= -3c² + 3c + 2c - 2 - c² + 2c = -4c² + 7c - 2
h) 2x²(x-5)-3x(x²-3x+5)= 2x³ - 10x² - 3x³ + 6x² - 15x = -x³ - 4x² - 15x
i) 6(a²+b+⅓)-6(a²-½)-3(b+⅓)= 6a² + 6b + 2 - 6a² + 3 - 3b - 1 = 3b + 4
j) 6x+12y/3+x-4y= 7x
k) 4*3p+6/12+10-p/15-9=
2009-10-03T15:28:45+02:00
A)3a²-15a+4a-20=3a²-11a-20
b)6-2√3+2√3-2=4
c)x²+2*x*2√2+8=x²+4√2x+8
d)4y²-8y+3y-6-8y+4y²=8y²-13y-6
e)6a²-2-a²+2a+2a+4=5a²+4a+2
f)5x²v²+5x²-x⁴-3x²-2x²-6=5x²v²-x⁴-6
g)-(3c²-3c-2c+2)-c²+2c=-3c²+3c+2c-2-c²+2c=-4c²+7c-2
h)2x³-10x²-3x³+9x²-15x=-x³-x²-15x
i)6a²+6b+2-6a²+3-3b-1=3b+1
j)6x+4y+x-4y=7x
k)12p+1/2+10-p/15-9=12p+1 1/2-p/15